Dental Lasers And Theır Use In Orthodontıcs - Serdar Üşümez; Aslıhan Üşümez (Galenos Yayinevi, 2002)
Since the invention of lasers in 1964, thousands of studies have been performed regarding their use in dentistry. This article presents a brief historical overview of lasers and their use in the field of dentistry focusing on orthodontics. Soft and hard tissue procedures, effects on dental materials, orthodontic enamel etching, adhesive curing, ceramic bracket debonding. adhesive remnant removal and diagnostic uses of lasers have been summarized. This article concludes with a summary of the limitations and advantages of laser dentistry and a point of view about their future in dentistry.